2009
DOI: 10.1111/j.1469-0691.2009.02908.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of CURB-65 with increasing age

Abstract: There has been concern about the performance of CURB-65 in older patients with community-acquired pneumonia (CAP) and that younger patients who subsequently die are initially misclassified as having non-severe CAP. The purpose of this study was to evaluate the effect of age on the performance of CURB-65. We analysed data prospectively, collected in two UK hospitals. Patients were stratified into four age cohorts. Mortality in each cohort was then stratified by CURB-65 score. Sensitivity, specificity, positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
5
30
0
Order By: Relevance
“…These results are in line with other reports hinting at an inferiorto-unacceptable operative performance of C(U)RB criteria [5,10] and C(U)RB-65 in elderly patients [4,11]. For example, PARSONAGE et al [11] found CURB-65 to be unreliable for the prediction of low risk in elderly patients, with mortality reaching 27% in the low-risk category in patients aged o80 years.…”
Section: Pulmonary Infections S Ewig Et Alsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in line with other reports hinting at an inferiorto-unacceptable operative performance of C(U)RB criteria [5,10] and C(U)RB-65 in elderly patients [4,11]. For example, PARSONAGE et al [11] found CURB-65 to be unreliable for the prediction of low risk in elderly patients, with mortality reaching 27% in the low-risk category in patients aged o80 years.…”
Section: Pulmonary Infections S Ewig Et Alsupporting
confidence: 90%
“…For example, PARSONAGE et al [11] found CURB-65 to be unreliable for the prediction of low risk in elderly patients, with mortality reaching 27% in the low-risk category in patients aged o80 years. In another study by CHEN et al [4] including in-and outpatients, the performance of both severity scores (CURB-65 and PSI) became significantly inferior with growing age: AUCs for CURB-65 were 0.80 (95% CI 0.67-0.93), 0.73 (95% CI 0.65-0.82) and 0.60 (95% CI 0.47-0.73) in the younger adult, elderly and very old patients, respectively.…”
Section: Pulmonary Infections S Ewig Et Almentioning
confidence: 99%
“…Two new scoring categories have since been proposed, extending the age and urea criteria to ≥85 years and ≥11 mmol/L, respectively, and with each scoring two points. Both cut-off points are considered to correlate with mortality 9 16 25. Extending the already adopted urea and age criteria allows a simple transition towards the use of the CURB-age score.…”
Section: Discussionmentioning
confidence: 99%
“…The A-DROP scoring system is a modified version of the CURB-65 and it is reported that performance of CURB-65 in mortality deteriorated with increasing age (≥65 years) [28]. AUC of ROC curves for mortality in A-DROP scoring system in this study, 0.8750 (95% confidence interval: 0.6300–1.0000) in those aged <65 years and 0.6374 (95% confidence interval: 0.3204–0.9544) in those aged ≥65 years, showed a similar trend.…”
Section: Discussionmentioning
confidence: 99%